Optimization of Parameters in Linear Active Disturbance Rejection Control via Differential Evolution Algorithm - Zhou Tao (Editorial Office of Aero Weaponry, 2021)
Two parameters of ω0 and ωc in the active disturbance rejection controller are automatically optimized via the differential evolution algorithm in this paper. First, the design of the second-order linear active disturbance rejection control (LADRC) is studied, then, the program flow chart and parameters selection methods of the differential evolution algorithm are analyzed. Simulation tests show that for the second-order system with large nonlinear total disturbance, the differential evolution algorithm can obtain global optimal values of two parameters and the fitness function reaches the minimum value fastly under conditions of the accurate and inaccurate parameter b, thus the system can achieve the higher step response speed and tracking precision. Moreover, this algorithm is also marked with the faster convergence rate, higher efficiency and precision, which can provide a novel practical method for automatic tuning of LADRC parameters.